Psychology of terrorism : coping with the continuing threat - Stout, Chris E. (Westport, Conn. : Praeger Publishers, 2004)
Selected chapters from the acclaimed 4-volume set, The Psychology of Terrorism.
Using psychology to counter terrorism at the personal and community level / Chris E. Stout -- Psychological issues in understanding terrorism and the response to terrorism / Clark McCauley -- Unresolved trauma : fuel for the cycle of violence and terrorism / Timothy Gallimore -- Us & them : reducing the risk of terrorism / Stephen D. Fabick -- Countering international terrorism : perspectives from international psychology / John M. Davis -- Honing a tool against terrorism : making United Nations peace operations more rapid and effective / Henry Breed -- Preventing terrorism : raising inclusively caring children in the complex world of the 21st century / Ervin Staub -- From terror to triumph : the path to resilience / Edith Henderson Grotberg.
Includes bibliographical references and index.
Print version record.
Keywords: Terrorism -- Psychological aspects; Prevention; POLITICAL SCIENCE -- Political Freedom & Security